Determining the direction of origin of a rock striking a moving vehicle windscreen. Issue 3 (4th May 2022) - Proctor-Parker, Craig; Stopforth, Riaan
Abstract: This paper is part of ongoing research and serves to document the testing of the direction of origin of a rock striking and passing through a windscreen of a motor vehicle. The paper covers the literature reviewed for the tests, the design of the test rig and the documentation of the tests performed. The data from the tests was gathered and analysed. Extensive video footage and imagery obtained was considered. As a result, it was deduced that given sufficient factors being evident, it is possible to determine the direction of origin of the rock.